Optimization of concentric array resonators for wide band noise reduction. (1st December 2016) - Coulon, Jean-Michel; Atalla, Noureddine; Desrochers, Alain
Abstract: In air duct noise control, Helmholtz resonators (HR) are considered as narrow band attenuators. For some applications they can be combined in line to form a wide band silencer. This study investigates the role of distance between HR side branch openings on the whole array attenuation. In the case of two resonators with same performance, the optimal distance can be calculated and corresponds to the quarter wave of HR mean frequency. On three or more HR arrays, relationships between resonators parameters and optimal lengths are much more complex. Tuning of such a device requires taking many geometrically coupled parameters into account; hence, design has to be automated. To operate this process, a 2D FEM COMSOL model has been coupled to a global MATLAB optimization solver. Among different types of constructions, arrays made of concentric resonators with transversal openings offers the most efficient and flexible design to optimize distance between openings. This methodology was applied to an existing turbo compressor silencer. Modifying openings and chambers arrangement, using the proposed approach increased the attenuation band by 10%. Another application concerning an air box for a two stroke engine was also investigated. This resulted in a 16L two chambers concept, being replaced by a more compact and more efficient, 8.3L wide band silencer, made of 8 resonators. With this approach it therefore becomes possible to handle available space and required noise attenuation on a required frequency band, all in one process.